2020
DOI: 10.33096/jifa.v12i1.619
|View full text |Cite
|
Sign up to set email alerts
|

UJI AKTIVITAS PENGHAMBATAN ENZIM α-GLUKOSIDASE EKSTRAK ETANOL BIJI BUAH ALPUKAT SANGRAI (Persea americana Mill.) SECARA IN VITRO

Abstract: It is known that the seeds of avocado (Persea americana Mill.) are one part of the avocado widely used to treat various diseases, including diabetes. Based on the previous research, avocado seeds contain flavonoids with the potency as inhibitors of the enzyme α-glucosidase. The research aimed to determine the potency of ethanol extracted by meceration using 96% ethanol. The inhibitory activity was assayed using ELISA (Enzyme-Linked Immunosorbant Assay) reader measured at the wavelength of 405 with an acarbose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…Inhibitory activity of α-glucosidase can be observed from the decrease in absorption at 305 nm, which indicates the absorption of p-nitrophenol formed. The substrate used was PNPG as a model that represents carbohydrates in the body, where the enzyme will break down the substrate into glucose and p-nitrophenol [5]. The result of this study showed that nano curcumin has a smaller IC50 value of 3.95 µg/ml compared to acarbose of 4.11 µg/ml, it is shown in fig.…”
Section: Fig 3: Inhibitory Activity Of α-Amylase For (A) Nano Curcumi...mentioning
confidence: 82%
See 2 more Smart Citations
“…Inhibitory activity of α-glucosidase can be observed from the decrease in absorption at 305 nm, which indicates the absorption of p-nitrophenol formed. The substrate used was PNPG as a model that represents carbohydrates in the body, where the enzyme will break down the substrate into glucose and p-nitrophenol [5]. The result of this study showed that nano curcumin has a smaller IC50 value of 3.95 µg/ml compared to acarbose of 4.11 µg/ml, it is shown in fig.…”
Section: Fig 3: Inhibitory Activity Of α-Amylase For (A) Nano Curcumi...mentioning
confidence: 82%
“…Then, 250 µl of 1% starch solution as a substrate and 250 µl iodine was added sequentially. Absorbance was measured at 595 nm by using UV-Visible spectrophotometer Thermo Scientific-Genesys 10S UV-Vis [5].…”
Section: Inhibitory Activity On α-Amylase Enzymementioning
confidence: 99%
See 1 more Smart Citation